Legal Protection for Insured Persons in the Life Insurance Claim Process at Insurance Companies Experiencing Bankruptcy - Elsa Mahriani Pasaribu; Adel Nazwa Sipa Sinaga; Wardiatul Hasanah Siregar; Irani Adwiyah Rambe4; Aicha Azdina Adly Fesya (ISNU Sumatera Utara, 2024)
Life insurance plays a significant role in providing financial protection against risks arising from death, disability, or other unforeseen events. However, the increasing number of cases involving insurance companies failing to fulfill their obligations to policyholders has raised serious concerns regarding legal protection, particularly when insurance companies face insolvency or bankruptcy. This study aims to analyze the legal responsibilities of life insurance companies in fulfilling policyholder claims and to examine the legal protection available to policyholders when insurance companies become bankrupt. This research employs a normative legal research method by examining primary and secondary legal materials, including statutory regulations, legal doctrines, and relevant literature. The findings indicate that a life insurance agreement constitutes a legally binding contract based on the principles of consensus, good faith, and reciprocal obligations between the insurer and the insured. Pursuant to Law Number 40 of 2014 concerning Insurance, insurance companies are legally obligated to maintain solvency and fulfill claim payments in accordance with policy provisions. In bankruptcy proceedings, policyholders are granted the status of preferred creditors, giving them priority over ordinary creditors in the distribution of bankruptcy assets. Nevertheless, practical implementation remains problematic due to weak regulatory supervision, limited public legal awareness, administrative obstacles in claim settlements, and the absence of a policy guarantee institution comparable to the Deposit Insurance Corporation in the banking sector. Therefore, stronger regulatory enforcement, improved supervision by the Financial Services Authority (OJK), greater public legal education, and the establishment of an insurance policy guarantee mechanism are necessary to ensure effective legal protection for policyholders and to strengthen public confidence in Indonesia's life insurance industry.